PENGGUNAAN SKEMA PEMAHAMAN BELAJAR PROJECT BASE LEARNING DENGAN MODEL E-BOOK PADA MATERI DASAR-DASAR KONSTRUKSI BANGUNAN - Nella Afidatus Sholehah (CV. ADIBA AISHA AMIRA, 2024)
The emergence of education is on the rise, fueled by the evolution of human intellect capable of instigating transformation. Among the educational frameworks in Indonesia is vocational education. Vocational education stands as a platform aimed at nurturing individuals' potential in both knowledge and skills to enable them to thrive in specific occupational fields. Within vocational education, the learning system is notably advantageous and scrutinized. Project Based Learning emerges as one of the learning methodologies viable within vocational education. This learning approach has been extensively adopted in developed nations like the United States. Termed as